Efficacy and safety of long‐acting recombinant fusion protein linking factor IX with albumin in haemophilia B patients undergoing surgery. (22nd June 2016) - Négrier, C.; Abdul Karim, F.; Lepatan, L. M.; Lienhart, A.; López‐Fernández, M. F.; Mahlangu, J.; Pabinger, I.; Li, Y.; Wolko, D.; Voigt, C.; Jacobs, I.; Santagostino, E.
Abstract : Introduction: Recombinant factor IX fusion protein (rIX‐FP) has been developed to improve the pharmacokinetic (PK) profile of factor IX (FIX), allowing maintenance of desired FIX activity between injections at extended intervals, ultimately optimizing haemophilia B treatment. Aim: To determine the efficacy and safety of rIX‐FP in the perioperative setting. Methods: Subjects were adult and paediatric patients with severe to moderately severe haemophilia B (FIX ≤ 2%) participating in three Phase III clinical trials and undergoing a surgical procedure. PK profiles were established prior to surgery for each patient. Haemostatic efficacy was assessed by the investigator for up to 72 h after surgery. Safety measurements during the study included adverse events and inhibitors to FIX. FIX activity was monitored during and after surgery to determine if repeat dosing was required. Results: Twenty‐one, both major and minor, surgeries were performed in 19 patients. Haemostatic efficacy was rated as excellent ( n = 17) or good ( n = 4) in all surgeries. A single preoperative dose maintained intraoperative haemostasis in 20 of 21 surgeries. Nine major orthopaedic surgeries were conducted in eight patients with a mean of 7 (range: 6–12) rIX‐FP injections during surgery and the 14‐day postoperative period. Median rIX‐FP consumption for orthopaedic surgeries was 87 IU kg −1 preoperatively and 375 IU kg −1 overall. No subject developed inhibitors to FIX or antibodies to rIX‐FP. Conclusion: Recombinant factor IX fusion protein was well tolerated and effectively maintained haemostasis during and after surgery. Stable FIX activity was achieved with a prolonged dosing interval and reduced consumption compared to conventional or currently available long‐acting recombinant FIX.